Consuming Urban Culture in Contemporary Vietnam, 1st edition - Drummond, Lisa (Routledge, 2020)
Vietnam is currently undergoing a metamorphosis from a relatively closed society with a centrally planned economy, to a rapidly urbanising one with a global outlook. These changes have been the catalyst for an exciting ferment of activity in popular culture. This volume contains contributions from scholars engaged in the most up-to-date social research in Vietnam, as well as some of Vietnam's most popular cultural producers who are forging new ways of imagining the present whilst at the same time engaging actively in reinterpreting the past. The diverse ways that Vietnam is culturally and socially negotiating the future are examined as the book addresses issues of indigenisation of cultural influences, ambivalence surrounding change, and the consistent blurring of boundaries between informal, non-state cultural activities and formal institutional structures in the evolution of a civil society in Vietnam.